Systemic reduced‐dose alteplase for diffuse pulmonary thrombi in a COVID‐19 patient - Yucel Colkesen (Clinical Case Reports)
Abstract Pulmonary embolism has a high frequency in COVID‐19 patients admitted to the intensive care unit. Low level of fibrinolysis is one of the asserted contributors to a prothrombotic state in COVID‐19. Thrombotic coagulopathy is mostly encountered as diffuse pulmonary thrombi. Diffuse pulmonary microemboli was treated successfully with reduced dose thrombolysis.